Rethinking the theory of evolution: New perspectives on human evolution and why it matters for Theology - Van Huyssteen, J. Wentzel (HTS teologiese studies, 2016)
This article addresses the issue of human imagination from the perspective of ‘niche construction’ in the wider discussion about ‘what makes us human’ and what it means to be a ‘self’, specifically for the Christian faith and for theology. In the article, a brief review of human origins and human evolution demonstrates the path and substantive impact of changes in behaviour, life histories and bodies in our human ancestors and us as humans ourselves. In the interactive process of niche construction, potentially changeable natural environments were, and are, acting continuously on variation in the gene pools of populations, and in this way gene pools were modified over generations. It is argued that a distinctively human imagination is part of the explanation for human evolutionary success and can be seen as one of the structurally significant aspects of the transition from earlier members of the genus Homo to ourselves as we are today. There is thus a naturalness to human imagination, even to religious imagination, that facilitates engagement with the world that is truly distinct. This provides fruitful addition to the toolkit of inquiry for both evolutionary scientists and interdisciplinary theologians interested in reconstructing the long, winding historical path to humanity.